Copper–phenanthroline catalysts for regioselective synthesis of pyrrolo[3′,4′:3,4]pyrrolo[1,2-a]furoquinolines/phenanthrolines and of pyrrolo[1,2-a]phenanthrolines under mild conditions - Paira, Rupankar; Anwar, Tarique; Banerjee, Maitreyee; Bharitkar, Yogesh P.; Mondal, Shyamal; Kundu, Sandip; Hazra, Abhijit; Maulik, Prakas R.; Mondal, Nirup B. (Beilstein Journal of Organic Chemistry, 2014)
A new series of pyrrolo[3′,4′:3,4]pyrrolo[1,2-a]furoquinolines/phenanthrolines and pyrrolo[1,2-a]phenanthrolines were efficiently built up from an 8-hydroxyquinoline derivative or phenanthroline via 1,3-dipolar cycloaddition reaction involving non-stabilized azomethine ylides, generated in situ from the parent furo[3,2-h]quinoliniums/phenanthroliums, in presence of a copper(II) chloride–phenanthroline catalytic system. The methodology combines general applicability with high yields.
Keywords: copper(II) chloride–phenanthroline; 1,3-dipolar cycloaddition; furo[3,2-h]quinoliniums; phenanthroliums; pyrrolo[1,2-a]phenanthrolines; pyrrolo[3′,4′:3,4]pyrrolo[1,2-a]furoquinolines/phenanthrolines